The people behind the pounds: a qualitative exploration of factors that help or hinder healthy, sustainable food purchases for people living with obesity and food insecurity in the UK - Hunter, Emma; Johnstone, Alexandra M.; Stone, Rebecca A.; Greatwood, Hannah C.; Hardman, Charlotte A.; Brown, Adrian; Griffiths, Claire; Douglas, Flora (Frontiers in Nutrition, 2025)
Good health is viewed as essential to enable citizens to live fulfilling lives, shape communities, and drive economic growth. However, health is socially patterned. Low socioeconomic status is associated with an increased risk of non-communicable diseases, where poor dietary patterns and diet-related obesity are likely contributors. Food purchasing can be influenced by many factors, including cost and income. Most food purchased to be consumed at home is acquired from supermarkets, and any increase in food prices disproportionately impacts low-income households, contributing to food insecurity. This study explored the factors that helped and hindered people living with obesity and food insecurity in purchasing healthy, environmentally sustainable food from supermarkets. Semi-structured interviews (n = 25) and focus groups (n = 7) were conducted between June and December 2023 with adults living in Scotland and England who self-identified as living with obesity and food insecurity. Using thematic analysis, six main themes were identified: (1) Supermarket deals: perceptions surrounding the good, the bad, and the ugly side of supermarket offers and promotions; (2) Skepticism about supermarkets and the wider food system: questioning supermarket pricing motives but recognizing the role of the wider food system in food pricing; (3) Other peoples’ role in enhancing or undermining healthy diet intentions: the impact of others in shaping food purchases; (4) Financial restrictions facing non-UK nationals: additional challenges faced by those with no recourse to public funds; (5) The overwhelming in-store supermarket experience: sensory overload and attempts to prevent unintended, impulse purchases; (6) Unconscious, environmentally sustainable shopping practices: cost saving practices that lead to environmentally sustainable purchasing patterns and behaviors as a unintentionally created outcome of budget maximizing strategies. However, such strategies, that is, limiting food waste and purchasing less meat, although beneficial for environmental sustainability, do not necessarily indicate that a healthier diet is being purchased or consumed. While views on some factors believed to help or hinder healthy, environmentally sustainable food purchases varied, there was general agreement amongst participants on the need for upstream changes, including having access to adequate benefits and wages.